ChemInform Abstract: Methanocarba Ring as a Ribose Modification in Ligands of G Protein Coupled Purine and Pyrimidine Receptors: Synthetic Approaches. Issue 25 (3rd June 2013) - Tosh, Dilip K.; Jacobson, Kenneth A.
Abstract Review: 49 refs.